Fluxos no mercado de trabalho e dinâmica do desemprego em diferentes horizontes temporais - Ajax Reynaldo Bello Moreira; Carlos Henrique Corseuil; Miguel N. Foguel (Instituto de Pesquisa Econômica Aplicada (IPEA), 2017)
– The functioning of the labor market can be represented by worker flows, and the fluctuation of these flows determines the fluctuation of unemployment. The literature measures the importance of a flow such as the proportion of the variance of long-term or stationary unemployment that is explained by the fluctuation of this component. This result is useful for analyzing short-term unemployment when long-term unemployment is a good proxy for short-term unemployment. Our contribution was to propose a decomposition of these kind of proxies using any period (h), which allows to explain the effect of the estimated transition in the period (t) on the unemployment rate in the periods (t + h). This construction puts in the same environment the effect of the short and long term transition on unemployment. It is worth mentioning that the trajectory of the decomposition factors does not always follow a monotonous trend, which makes more important the consideration of the intermediate periods.
Keywords: E24; E32; J63; 330; unemployment; flows; decomposition